A Comprehensive Study of Inter-relationship of Literature and Journalism. - Dr. Nasir Afridi; Dr. Zeenat Bibi (Zaban-o-Adab, 2021)
The relationship between literature and journalism is a controversial issue. Some of the literary figures acknowledge the supremacy of Journalism over Literature while some of them claim contrary. Though, in the beginning both the areas were considered not that much distinct. With the passage of time both areas enhanced their needs and reservations. For both the life was prime focus. Owing to color some needs and requirement, Journalism and literature are dealt differently. Journalism adopts the measures of urgency while Literature effects in long-run. However, Journalism and Literature are the two facets of the same coin and cannot be dealt distinctly. The Subject under Consideration carries out a comprehensive study of the inter-relationship of Journalism and Literature.